STUDI KRITIS UNDANG-UNDANG PERKAWINAN NO. 1 TAHUN 1974 REVISI UU NO. 16 TAHUN 2019 TENTANG BATAS USIA PERNIKAHAN DAN PENERAPANNYA DI MASYARAKAT - Damayanti, Ima (Bajang Institute, 2025)
This study, entitled “A Critical Study of Marriage Law No. 1 of 1974 Revised by Law No. 16 of 2019 on the Minimum Age of Marriage and Its Implementation in Society,” examines the legal revision that equalized the minimum age of marriage for men and women at 19 years. This amendment aims to protect children's rights and reduce early marriages. Employing a juridical-sociological approach, this research analyzes existing legal provisions and observes their implementation in society. Using a library research approach, this study explores both primary and secondary data by reading and thoroughly examining materials related to the research problem. Data were collected through literature review. The results indicate that although the revised law provides a stronger legal foundation, its application still faces challenges. Social, cultural, and economic factors contribute to the high number of marriage dispensation requests granted by courts, allowing underage marriages to persist. Therefore, enhanced legal education, stricter regulation of dispensations, and active involvement of the government and community leaders are necessary to curb early marriages. Thus, the intended objectives of the legal amendment to protect children's rights can be more effectively realized